SAFETY TALK COMMUNICATION STRATEGY AT PT. COALINDO ADHI PERKASA - Sapitri; Priatna (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2025)
Work safety is a crucial aspect in the mining industry due to the high risks of accidents that may occur. PT. Coalindo Adhi Perkasa, as a mining company, is committed to creating a safe working environment through various efforts, one of which is the regular implementation of safety talk. This study aims to describe the communication strategies applied in conducting safety talk at PT. Coalindo Adhi Perkasa and how these strategies are implemented. The research uses a qualitative method with a case study approach, where data are collected through in-depth interviews with management and employees, direct observation during the sessions, and documentation review related to the materials and communication processes. The findings reveal that the communication strategy in safety talk at PT. Coalindo Adhi Perkasa emphasizes an interactive approach that encourages active employee participation, the use of simple language, and the utilization of visual media and real-life case examples relevant to daily work. Furthermore, full support from management and the consistency of safety talk implementation are important factors in executing the communication strategy. Adaptive and innovative communication strategies were also found to tailor the material according to the needs and conditions on site, thus helping to build a strong safety culture within the workplace.